Pengembangan Unit Pengumpul Zakat (UPZ) UIN Sunan Ampel Surabaya: Telaah Strategi dan Implementasinya - Faizal Yulianto; Lilik Rahmawati (Management of Zakat and Waqf Journal (MAZAWA), 2021)
The research entitled "Development Strategy for the Zakat Collection Unit (UPZ) of the State Islamic University of Sunan Ampel Surabaya" is a study that aims to answer questions about the development strategy of the Zakat Collection Unit (UPZ) of the Sunan Ampel State Islamic University, Surabaya.  The research method used in this research is a qualitative research method with a descriptive approach.  Data collection methods used in this study by means of interviews and documentation.  The development strategy that has been carried out by UPZ UIN Sunan Ampel Surabaya includes, changing the Rector's Decree of UIN Sunan Ampel Surabaya to become SK UPZ BAZNAS East Java, conducting a comparative study to UIN North Sumatra and UIN Maulana Malik Ibrahim Malang, and collecting in three ways, namely, picking up zakat.  directly to muzakki, bank transfer, and via barcode code.  The development strategy that has been carried out by UPZ UIN Sunan Ampel Surabaya is not optimal.  UPZ UIN Sunan Ampel Surabaya must maximize the supporting factors of its development and find the right solution in overcoming the existing inhibiting factors so that zakat management at UPZ UIN Sunan Ampel Surabaya runs optimally.